2022
DOI: 10.1007/s00520-022-06890-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Siriraj, in-house-developed, frozen gloves for cold therapy reduction of chemotherapy-induced peripheral neuropathy in gynecological cancer patients: randomized controlled trial

Abstract: Objectives The primary objective of this study was to investigate the efficacy of cold therapy in reducing paclitaxel-based, chemotherapy-induced, peripheral neuropathy (CIPN). The secondary objective was to establish the incidence of CIPN arising from paclitaxel administration. Materials and methods The study enrolled gynecological cancer patients who were aged over 18 years and receiving chemotherapy which included paclitaxel (175 mg/m2 every 3 weeks). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Additionally, four studies used interventions pooled as ME [ 28 , 33 , 34 , 37 ], and 13 studies used interventions pooled as UCP. One three-arm trial [ 31 ] conducted a direct comparison of sensorimotor training (SMT), WBV, and UCP, two used cryotherapy [ 32 , 38 ], six used Acu [ 25 , 30 , 35 , 36 , 39 , 40 ] and one used ultrasound and multicomponent exercise (USME [ 34 ]). The close loop of the network map was formed by SMT, WBV, and UCP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, four studies used interventions pooled as ME [ 28 , 33 , 34 , 37 ], and 13 studies used interventions pooled as UCP. One three-arm trial [ 31 ] conducted a direct comparison of sensorimotor training (SMT), WBV, and UCP, two used cryotherapy [ 32 , 38 ], six used Acu [ 25 , 30 , 35 , 36 , 39 , 40 ] and one used ultrasound and multicomponent exercise (USME [ 34 ]). The close loop of the network map was formed by SMT, WBV, and UCP.…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analysis was performed by different scales. Among the studies, 15 applied the FACT/GOG-Ntx subscale for assessment [15,25,28,[30][31][32][33][34][35][36][37][38][39][40][41], involving 667 participants. A higher score of this subscale indicated more mild neuropathological symptoms.…”
Section: Peripheral Neuropathological Symptomsmentioning
confidence: 99%
“…6,8 One prospective randomized trial in gynecologic cancer found that cryotherapy significantly reduced subjective chemotherapy-induced neuropathy using the FACT/ GOG-NTX. 24 Compression alone has been evaluated in breast cancer and resulted in significantly reduced neuropathy compared with no intervention. 25 Another study in breast cancer compared cryotherapy to compression therapy and found no difference in the incidence of peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal therapies such as frozen gloves have been investigated primarily for their preventive effects. Thermoregulatory effects delivered by cryocompression were well-tolerated and were found to significantly reduce the incidence of CIPN (Bandla et al, 2020;Oneda et al, 2020;Chitkumarn et al, 2022). One study has investigated the benefit of combination therapy and implemented a 15-week integrated program of massage, passive mobilization and physical exercises with or without whole body vibration and patients reported less pain and improved function over time (Schönsteiner et al, 2017).…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%